Two new records of Agaricus from Southwest China - Mao Qiang He (2018)
© 2016. Mycotaxon, Ltd. Two specimens of A. brunneosquamulosus (from China and Thailand) and four specimens of A. duplocingulatus (from China) were identified and studied by morphological and ITS sequence analyses. They are presented here with descriptions, line drawings, and color photographs as new records for China. Our additional molecular sampling of A. duplocingulatus has revealed intraspecific variability within this species.